Challenges faced by orthopaedic trainees during the Covid-19 pandemic – An Irish perspective. Issue 5 (October 2021) - Clesham, Kevin; Hughes, Andrew; Feeley, Iain; Sheehan, Eoin; Mohamed, Khalid Merghani Salih
Abstract: Background: The recent SARS-CoV2/COVID-19 pandemic has caused a change in most aspects of our daily lives. Our health systems have had to adjust at an unprecedented rate to accommodate care for patients affected by the virus. As a result there has been widespread disruption to trauma and elective services throughout the Orthopaedic community Worldwide. We discuss the changes facing orthopaedic residents in training and the adaptations that have been made. Methods: We discuss the challenges posed from a reduction in caseload to surgeons in training, teaching activities, patient interaction, workforce reinforcement and support networks in Ireland. Results: A structured deployment of residents has taken place ensuring maximum exposure to operative cases to maintain competency. Teaching activities have been virtualised into a new curriculum that provides trainees with convenient access to a wide range of specialists at defined time periods during the week. Strategies have been employed to reinforce the workforce in anticipation of an acute reduction in staff due to the Covid-19 virus. Conclusions: The changes have been rapid and despite many of these adjustments being borne out of necessity, the innovation displayed will almost certainly alter how training is ultimately delivered long after the crisis has ceased. Highlights: Practical and Educational parts of Spr training have been affected by the pandemic Learning requirements have been met through a rapid transition to online education Multiple strategies employed in Orthopaedics to ensure competence maintained